2012
DOI: 10.1007/s00702-012-0910-z
|View full text |Cite
|
Sign up to set email alerts
|

The dynactin p150 subunit: cell biology studies of sequence changes found in ALS/MND and Parkinsonian Syndromes

Abstract: The dynactin p150glued subunit, encoded by the gene DCTN1 is part of the dynein-dynactin motor protein complex responsible for retrograde axonal transport. This subunit is a candidate modifier for neurodegenerative diseases, in particular motoneuron and extrapyramidal diseases. Based on an extensive screening effort of all 32 exons in more than 2,500 ALS/MND patients, patients suffering from Parkinsonian Syndromes and controls, we investigated 24 sequence variants of p150 in cell-based studies. We used both no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Moreover, Stockmann et al identified 24 exonic variants among more than 2,700 mixed samples comprised of 1,708 sporadic ALS, 218 striatal diseases (multiple system atrophy, PSP, and HD), and 778 healthy controls. However, none of them had confirmed segregation in affected family members, and some of them were found in both the disease and control groups [52]. Therefore, with the exception of the p.Gly59Ser mutation seen in the HMN7B family, the pathogenicity of these DCTN1 variants identified in non-PS phenotypes remains to be established.…”
Section: Dctn1 Mutations/polymorphisms Associated With Other Phenotmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Stockmann et al identified 24 exonic variants among more than 2,700 mixed samples comprised of 1,708 sporadic ALS, 218 striatal diseases (multiple system atrophy, PSP, and HD), and 778 healthy controls. However, none of them had confirmed segregation in affected family members, and some of them were found in both the disease and control groups [52]. Therefore, with the exception of the p.Gly59Ser mutation seen in the HMN7B family, the pathogenicity of these DCTN1 variants identified in non-PS phenotypes remains to be established.…”
Section: Dctn1 Mutations/polymorphisms Associated With Other Phenotmentioning
confidence: 99%
“…However, functional analyses of the ALS-associated mutant p150 Glued (p.Met571Thr, p.Arg785Trp, p.Arg1101Lys, and p.Thr1249Ile) did not show any deficits. Microtubule binding abilities were preserved in all these mutations, and no aggregations were observed in the mutant-overexpressed culture cells [52, 64]. …”
Section: The Relevance Of Dctn1 Mutations To Neurodegenerationmentioning
confidence: 99%
“…For example, p150 mutants found in patients impact the subcellular localization of p150 in motoneurons [Stockmann et al, 2013]. However, mutations within the microtubule-binding domain of p150…”
Section: Introductionmentioning
confidence: 99%
“…This is also reflected in the zebrafish dync1h1 (cannonball) mutant, which displays abnormal organelle positioning and accumulation of Golgi-associated vesicles in the inner segment of the retina (Insinna et al, 2010) and Schwann cell deficient myelination (Langworthy and Appel, 2012), a symptom common to NDDs. Additionally, dynactin mutations have been found in patients with amyotrophic lateral sclerosis and Perry syndrome (Stockmann et al, 2013). Death of sensory neurons and axonal degeneration is also reported in zebrafish with morpholino knockdown of dctn1a, dctn1b and dctn2a (Insinna et al, 2010) and the mutants dctn1a (mikre oko) (Tsujikawa et al, 2007) and dctn2 (ale oko) (Jing and Malicki, 2009).…”
Section: Zebrafish Tools To Study Microtubulesmentioning
confidence: 96%